2005
DOI: 10.1507/endocrj.52.241
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Levels and Cardiovascular Risk Factors in Japanese Men with Type 2 Diabetes

Abstract: Abstract. Several cardiovascular risk factors correlate with adiponectin levels. It is not known whether total homocysteine, folate and g-glutamyl transferase levels correlate with adiponectin. We cross-sectionally analyzed the association between adiponectin and these cardiovascular risk factors in diabetic patients. One hundred and two male inpatients with type 2 diabetes without overt nephropathy or insulin use were studied. In a regression analysis of the quartiles of adiponectin, plasma levels of adiponec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
(33 reference statements)
2
13
0
Order By: Relevance
“…Administration of recombinant adenovirus expressing human adiponectin to apoE-deficient animals causes a 30% reduction in the formation of atherosclerotic lesions in the absence of any effects on metabolic traits (83,84). Consistent with these findings, men with adiponectin levels in the highest quartile have been shown to have a significantly lower incidence of cardiovascular disease than men with adiponectin levels in the lowest quartile, independently of other cardiovascular risk factors or systemic inflammation markers (85,86). Studies of the association between adiponectin polymorphisms and cardiovascular outcomes have not been as numerous as those concerning adiponectin levels or metabolic traits, but the overall number of study subjects is such that some preliminary conclusions can be drawn.…”
Section: Impact Of Adipoq Gene Variants On the Risk Of Coronary Artersupporting
confidence: 55%
“…Administration of recombinant adenovirus expressing human adiponectin to apoE-deficient animals causes a 30% reduction in the formation of atherosclerotic lesions in the absence of any effects on metabolic traits (83,84). Consistent with these findings, men with adiponectin levels in the highest quartile have been shown to have a significantly lower incidence of cardiovascular disease than men with adiponectin levels in the lowest quartile, independently of other cardiovascular risk factors or systemic inflammation markers (85,86). Studies of the association between adiponectin polymorphisms and cardiovascular outcomes have not been as numerous as those concerning adiponectin levels or metabolic traits, but the overall number of study subjects is such that some preliminary conclusions can be drawn.…”
Section: Impact Of Adipoq Gene Variants On the Risk Of Coronary Artersupporting
confidence: 55%
“…These results are consistent with reported findings. [22][23][24] We observed a lower serum level of adiponectin in MetS groups than in non-MetS groups. Serum levels of adiponectin correlating with serum HDL-C levels showed that serum adiponectin as well as HDL-C were lower in CHD patients than in non-CHD patients, findings which were consistent with previously reported findings that circulating levels of adiponectin were lower in patients with CHD than in controls, even when BMI and age were matched.…”
Section: Discussionmentioning
confidence: 98%
“…The present results also demonstrated that circulating adiponectin levels were significantly decreased in the obese young women. Adiponectin levels have also been found to decline concurrently with progression of insulin resistance [29], and to decrease in middle-aged subjects who have obesity, cardiovascular risk factors, coronary artery disease or type 2 diabetes [30][31][32]. Although it is not clear whether long-standing low adiponectin levels from an early age has an adverse effect, it appears of great importance to elucidate the mechanisms underlying the low adiponectin levels not only in middle-aged subjects but also in young subjects to prevent lifestyle-related diseases.…”
Section: Discussionmentioning
confidence: 99%